2019
DOI: 10.1109/jstqe.2019.2918930
|View full text |Cite
|
Sign up to set email alerts
|

First Near-Ultraviolet- and Blue-Enhanced Backside-Illuminated Single-Photon Avalanche Diode Based on Standard SOI CMOS Technology

Abstract: We present the world's first backside-illuminated (BSI) single-photon avalanche diode (SPAD) based on standard silicon-on-insulator (SOI) complementary metal-oxidesemiconductor (CMOS) technology. This SPAD achieves a good dark count rate (DCR) after backside etching, comparable to DCRs of BSI SPADs fabricated on bulk wafers. Unlike bulk-wafer-based BSI SPADs, which typically suffer from poor violet and blue sensitivity, the proposed BSI SPAD features increased near-ultraviolet sensitivity as well as significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…The world's first backside‐illuminated (BSI) single‐photon avalanche diode fabricated with standard SOI CMOS technology is shown in Figure 7b. [ 42 ] This device achieves a good dark count rate (DCR), comparable with DCRs of BSI SPADs fabricated on bulk wafers. In addition, this SPAD features increased sensitivity in near‐ultraviolet, violet, blue, and also a wide wavelengths spectrum.…”
Section: Photodetectors With High Internal Gainmentioning
confidence: 93%
“…The world's first backside‐illuminated (BSI) single‐photon avalanche diode fabricated with standard SOI CMOS technology is shown in Figure 7b. [ 42 ] This device achieves a good dark count rate (DCR), comparable with DCRs of BSI SPADs fabricated on bulk wafers. In addition, this SPAD features increased sensitivity in near‐ultraviolet, violet, blue, and also a wide wavelengths spectrum.…”
Section: Photodetectors With High Internal Gainmentioning
confidence: 93%
“…Similarly, Morgan et al 44 demonstrated an improvement in the responsivity of an evanescently coupled PD by arranging doped regions as fingers. Additionally, reducing the dark counts of the SPAD can be achieved by introducing a doped isolation layer between the junction and the substrate or using a silicon-oninsulator (SOI) substrate to reduce the volume of the detector and to prevent undesired charged carriers from reaching the active region of the SPAD 23,[45][46][47][48] . These refinements of the junction design have the potential to significantly improve the performance of the waveguide-coupled Si SPADs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The BSI configuration is mainly used for near-infrared applications [ 70 , 95 ], where photons are absorbed over tens of microns. A recent work shows that some blue-enhanced/NUV architectures are also possible for the BSI configuration [ 110 ]. The FSI approach works mainly for the blue and UV range of the spectrum, since the penetration depth of these photons is below one micron ( Figure 11 ) and therefore, inside the depleted region.…”
Section: Perspective Of 3d Pdc For Radiation Instrumentationmentioning
confidence: 99%